The Modern Corporation and Campaign Finance: Incorporating Corporate Governance Analysis into First Amendment Jurisprudence - Thomas W. Joo (Washington University Law Quarterly, 2001)
This Article argues that the First Amendment analysis of corporate campaign finance regulations, such as those in Senate Bill 27, should recognize the institutional peculiarities of business corporations. Courts have sometimes treated business corporations as if they were identical to individuals for constitutional purposes. But political spending by corporations should be distinguished from the political spending of individuals (and from that by labor unions and nonprofit organizations). Despite the tendency to treat corporations like individuals, courts have at other times upheld special restrictions on corporations based on the naked assertion that states have special power to regulate corporations. The First Amendment analysis of corporate campaign finance regulation should be firmly grounded on corporate institutional characteristics and avoid the tendency toward conclusory reasoning.
Keywords: Campaign funds; Corporate speech; Corporate governance; Freedom of speech; Political campaigns